Pragmatismo Americano: O Direito de Crer diante da Morte de Deus (American Pragmatism: The Right to Believe ahead the Death of Good) - DOI: 10.5752/P.2175-5841.2010v8n18p104 - Mattos, Rafael da Silva (Horizonte, 2010)
Pragmatism is a philosophical movement that includes those who claim that a proposition is true if it works satisfactorily, and that the meaning of a proposition is to be found in the practical consequences of accepting it, and that unpractical ideas are to be rejected. The Pragmatism began in the late nineteenth century with Charles Sanders Peirce (How to Make Our Ideas Clear; The Fixation of Belief) and it was developed further in the works of William James (Peirce and James were members of The Metaphysical Club). The Pragmatism has a major idea: truth is mutable. This article is a theoretical-conceptual discussion about the right to believe, from the perspective of pragmatist philosophy of William James. The article begins with a brief discussion about religion, and then discusses the position of Nietzsche and, finally, the perspective of American philosophy created by the pragmatist Charles Peirce and William James is discussed.